PENGARUH LATIHAN SENAM AEROBIK TERHADAP DISABILITAS AKIBAT LOW BACK PAIN PADA WANITA POSTPARTUM 17-26 MINGGU - Lucky Anggiat (Jurnal Pro-Life, 2019)
This study purpose is to analyze the effects of aerobic exercise interventions toward low back pain for 17-26 Weeks postpartum women in Sukabumi, West Java 2014. This study was aquasi-experimental with pre and post design. The total population are 40 people from vaginal delivery and section caesarea and they are measured by Oswestry Disability Index for low back pain (ODI); the total subject for study are 25 subjects and quared of value p=0.05 (p< 0.05) by dependent T test. The study showed the effect of aerobic exercise intervention toward the decrease disability of low back pain for postpartum women. It is caused by result of difference ODI score from pre (13.96±3.8) and post (4.6 ± 4.36) intervention 9,36 ± 0,86 and the result value of dependent T test is p=0.00 (p<0,05). There was the effect of aerobic exercise intervention in decreasing disability of low back pain for 17-26 weeks postpartum women. Keywords: Aerobic Exercise, Low Back Pain, OD , Postpartum